THE EFFECT OF USING WORD CLAP GAME ON THE VOCABULARY MASTERY - Putu Tressya, Susanti; Sudirman, Sudirman; I Putu Indra, Kusuma (Lingua Scientia, 2018)
This study aimed at investigating whether or not there was a significant effect of using Word Clap Game on the vocabulary mastery of the fifth grade students of SD Negeri 1 Banjar Jawa. The research was true experimental with Post-test Only Control Group Design. The population was the fifth grade students of SD Negeri 1 Banjar Jawa. Cluster Random Sampling was assigned to select the sample of the study. The samples were 30 students at grade 5A for experimental group and 30 students at grade 5B for control group. Those two groups were determined by lottery. The experimental group was taught by using Word Clap Game and the control group was taught by using conventional teaching technique. The data were analyzed by using T-test through SPSS program. The result of the data analysis showed that students in experimental group performed better than the students in control group. It was proven by the result of the descriptive statistics that showed the mean score of the experimental group was 89,33 while the mean score of the control group was 84,67. The result of the t-test also showed that the value of the tobs was greater than the tcv where the tobs was 2,586 while the tcv was 1,672. Based on the findings, it was concluded that there was a significant effect of using word clap game on the students’ vocabulary mastery rather than using conventional teaching.